SOKOTO JIHAD LITERATURE AND THE ATTITUDE OF MUSLIMS TOWARDS ITS STUDY AND UTILIZATION - Bashar, Tambari Abbas (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
The Sokoto Jihad was a major Islamic movement in the 19th century West Africa. The Sokoto Jihad brought profound transformations in the social, political and economic spheres of Hausaland and beyond. Some of such changes include the establishment of the Sokoto Caliphate, the revival of Islam, and the development of learning and scholarship. In fact, the intellectual development brought by the Jihad was the most important impact of the movement the development of knowledge as valuable machinery in the spread and development of Islam. This paper therefore looks at the attitude of Muslims to the study and utilization of the Sokoto Jihad literature. It is however observed that lack of the knowledge and understanding of Arabic is one of the causes of lack of concern. The maghribi style of writing also led to the weary attitude the Muslims to the study and use of the jihad literature. Not only that, it is also observed in the paper that Muslim youths are addicted to other foreign writings and for that look down upon the works of the jihad leaders. The review of existing literature and interview was adopted as a method in the collection of data. It was also recommended that the states of Sokoto, Kebbi and Zamfara governments should as a matter of fact come in to revive the writings of the Jihad leaders and their followers.